2021
DOI: 10.18632/aging.203416
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA GACAT1 targeting miRNA-149 regulates the molecular mechanism of proliferation, apoptosis and autophagy of oral squamous cell carcinoma cells

Abstract: To explore the effects of lncRNA GACAT1/miR-149 molecular axis on the proliferation, apoptosis, migration and autophagy of oral squamous cell carcinoma (OSCC) cells, and to explore its molecular mechanism. The expressions of lncRNA GACAT1 and miR-149 in tissues and cell lines of patients with OSCC were detected by qRT-PCR. Si-control, GACAT1-siRNA, inhibitor NC and miR-149 inhibitors were transfected into OSCC cells separately or in combination with Lipofectamine 2000. The binding sites between lncRNA GACAT1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Moreover, FGF9 high expression in CAFs of lymph node metastatic sites was associated with poor prognosis in GC [60][61][62]. MiRNA-149 also plays a role in inhibiting tumor [63][64][65][66][67].…”
Section: Cytokines and Chemokines During Tumor Progression Different ...mentioning
confidence: 99%
“…Moreover, FGF9 high expression in CAFs of lymph node metastatic sites was associated with poor prognosis in GC [60][61][62]. MiRNA-149 also plays a role in inhibiting tumor [63][64][65][66][67].…”
Section: Cytokines and Chemokines During Tumor Progression Different ...mentioning
confidence: 99%
“…Furthermore, GACAT1 knockdown promoted autophagy and apoptosis while inhibiting proliferation and metastasis in OSPECAPJ41 and HSC-4CC OSCC cell lines. Interestingly, when the miR-149 inhibitor was applied, the results were reversed, indicating that the lncRNA GACAT1 and miR-149 are promising therapeutic targets in OSCC ( Chen et al, 2021 ). Similarly, in HSC-3 and HSC-4 OSCC cell lines, autophagy and proliferation were inhibited by the effect of miR-1301-3p on the carcinogenic gene lactate dehydrogenase A (LDHA), and apoptosis was promoted.…”
Section: Autophagy-related Biomarkers In Osccmentioning
confidence: 99%
“…Another study by Chen et al. showed that when the gastric cancer-associated transcript 1 (GACAT1) was inhibited in OSCC samples, it promoted apoptosis and autophagy, mainly related to the targeting of miRNA-149 ( 93 ). Long intergenic non-coding RNA 01207 (LINC01207) and LINC00958 were also upregulated in OSCC tissues and cells.…”
Section: Lncrnas In Drug Resistance Mechanismsmentioning
confidence: 99%